2018
DOI: 10.11606/s1518-8787.2018052000413
|View full text |Cite
|
Sign up to set email alerts
|

Burden of ischemic heart disease mortality attributable to physical inactivity in Brazil

Abstract: OBJECTIVE To analyze if the burden of ischemic heart disease mortality trend attributed to physical inactivity in Brazil differs from the global estimates.METHODS Databases from the Global Burden of Disease Study for Brazil, Brazilian states, and global information were used. We estimated the summary exposure value for physical inactivity, the total number of deaths, and the age-standardized death rates for ischemic heart disease attributed to physical inactivity in the years 1990 and 2015, and the population-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
(37 reference statements)
2
6
0
3
Order By: Relevance
“…The present study found that from 1990 to 2017, Brazilian states with the lowest SDI and with the greatest social discrepancies had lower reductions in age-standardized mortality rates for all causes due to physical inactivity when compared to states with better economic development. This finding reinforces two problems that have already been presented in literature [ 18 , 28 ]: (1) physical inactivity is a serious problem in economically disadvantaged populations; (2) social and economic inequalities present in these states are reflecting on the health of the population, causing greater difficulty in reducing physical inactivity. Thus, increasing the level of physical activity of the population in order to reduce the risks of early mortality and morbidity due to noncommunicable chronic diseases should include efforts to improve the living conditions and reduce inequities of the population and not only isolated physical activity promotion actions.…”
Section: Discussionsupporting
confidence: 89%
“…The present study found that from 1990 to 2017, Brazilian states with the lowest SDI and with the greatest social discrepancies had lower reductions in age-standardized mortality rates for all causes due to physical inactivity when compared to states with better economic development. This finding reinforces two problems that have already been presented in literature [ 18 , 28 ]: (1) physical inactivity is a serious problem in economically disadvantaged populations; (2) social and economic inequalities present in these states are reflecting on the health of the population, causing greater difficulty in reducing physical inactivity. Thus, increasing the level of physical activity of the population in order to reduce the risks of early mortality and morbidity due to noncommunicable chronic diseases should include efforts to improve the living conditions and reduce inequities of the population and not only isolated physical activity promotion actions.…”
Section: Discussionsupporting
confidence: 89%
“…Another limitation was the failure to analyze the economic austerity measures taken by each Brazilian state in the specific period of economic crisis, as each Brazilian state could, for example, have different taxation measures in relation to the federal government. Another limitation of this research was the calculation of physical activity only by surveys that used self-reported measures, whose estimates have higher risk of bias compared to objective measures ( Silva et al, 2018 ). Other limitations of estimation models are evidenced in literature ( GBD 2017 Risk Factor Collaborators, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…A diferencia de este resultado, estudios previos que verificaron los niveles de actividad física en el tiempo libre en los adultos mayores identificaron que la prevalencia aumenta con la edad (37,38) , aunque estos estudios no realizaron análisis estratificados de acuerdo con la situación conyugal de los adultos mayores. Una posible razón para el resultado encontrado en el presente estudio puede deberse al sesgo de supervivencia, dado que la inactividad física está asociada con la mortalidad, es posible que muchas personas de edad avanzada que murieron antes de cumplir 70 años hayan estado en promedio menos activas físicamente que los que alcanzaron esta edad (39,40,41) . Otra posible explicación puede ser el hecho de que probablemente haya una mayor proporción de jubilados entre aquellos con 70 a 79 años que entre los con 60 a 69 años, y es plausible imaginar que los jubilados tengan más tiempo libre y puedan ser más activos en este dominio que las personas no jubiladas.…”
Section: Discussionunclassified